Evaluation the Efficacy of Ozone and High Temperature to Control Egges and Pupae Stages Laboratory for Hairy Grain Beetle (khapra) Trogoderma granarium Everts Coleoptera : Dermestidae - A. Sabet, Falah; H.Sabr, Saadi (Iraqi Journal of Science, 2023)
The effect of the treatments were the combination of ozone gaz with hightemperatures ( 35، 40 and 45C) and tempreture alone in addition to control treatmenttreatments were tested on Egges and Pupae stages of hairy grain beetleTrogoderma granarium (Everts). Results showed that( Z+H) and (H) treatmentswere more lethally effective (100%mortality) than to control treatment on Eggesand Pupae stages of insect . The results also showed that first treatment(Z+H) wasmore effective than the second treatment (H) on two stages , 1Tthe total1T 1Tkillings1T 1T100% (LT100)1T 1Tin eggs1T 1Treached at1T 1Tperiods1T 1T15.001T, 1T13.001T 1Thours and1T 1T18 minutes1T, respectively1Twith treatment of1T 1Tthe 1Tozone gaz with high temperatures ( 35، 40 and 45C),whentempreture alone showed 1Texposure to1T 1T0.01T, 1T0.01T 1Tand 30 minutes1T. 1TResult showed alsothe pupae stage was1T 1Tmore resistant1T than egg stage 1Tthe time required1T 1Ttoachieve1T 1T100%1T 1Tkill1T 1Tratio1T 1Tis1T 1T15.001T, 1T13.301T 1Tand1T 1T1.001T 1Thours1T, respectively, 1Tand1T 1Tin thetreatment of1T tempreture alone showed 1Texposure to1T 1T0.01T, 1T0.01T 1Tand1T 1T1.151T 1Thours1T,respectively. ,the temperature alone treatment with 35,40C was not effective onEgg and Pupae while the temperature 45C alone and combined with Ozone gaz wasmore effective on two stages of insect .It was also found that Egg stage was moresensetive to all treatments than Pupae stage at 45 Celsius